(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
This contribution is focused on the main questions involving claims for damages about wrongful birth and wrongful life. The Italian jurisprudence is divergent in drawing the most balanced solutions about evidence and causation: a decision of the Joined Chambers of the Court of Cassation is now awaited.